Exploring the relationship between personal and cohabiting family members’ COVID-19 infection experiences and fear of COVID-19: a longitudinal study based on the Japan COVID-19 and Society Internet Survey (JACSIS) - Takahiro Tabuchi; Akira Ishikawa; Hirokazu Tachikawa; Haruhiko Midorikawa (BMJ Open)
Objectives This study aims to explore the relationship between the combined experiences of COVID-19 infection in individuals and their family members and the resulting fear of COVID-19, with a focus on the severity of symptoms and various sociodemographic factors.Design Longitudinal survey study.Setting The Japan COVID-19 and Society Internet Survey (JACSIS), a large-scale web panel survey administered in Japan.Participants Analysis was based on responses from 15 542 individuals who participated in all three waves of JACSIS conducted between 2020 and 2022.Main outcome measures The primary measure was the fear of COVID-19, assessed using the Fear of COVID-19 Scale. The study employed a two-way analysis of variance without repetition, Games-Howell post hoc tests and ordinary least-squares linear regression analysis, with time points treated as fixed effects.Results The study revealed significant differences in fear levels based on the combined COVID-19 infection experiences of respondents and their family members, with variations observed across different time points. Mild symptoms in either the respondents or their family members correlated with reduced fear (β=−0.584, SE=0.181, p=0.001), while severe symptoms were associated with increased fear (β=1.244, SE=0.217, p<0.001). Gender, age, marital status and a history of respiratory disease or mental illness were also significant factors. For instance, females reported higher fear levels compared with males (β=0.707, SE=0.049, p<0.001), and those with a history of respiratory diseases showed increased fear (β=1.632, SE=0.286, p<0.001). Over time, the general fear of COVID-19 decreased, with the sharpest decline observed at T3 compared with T1 (β=−1.399, SE=0.061, p<0.001).Conclusion The study highlights the significant influence of the combined COVID-19 infection experiences of individuals and their family members (the severity of symptoms, in particular) on the fear of COVID-19. These results underscore the need for tailored mental health interventions that consider both personal and familial infection experiences, as well as other sociodemographic factors. The findings also reflect the evolving public response to the changing dynamics of the pandemic.